Not so bad after all: retroviruses and long terminal repeat retrotransposons as a source of new genes in vertebrates. (April 2016) - Naville, M.; Warren, I.A.; Haftek-Terreau, Z.; Chalopin, D.; Brunet, F.; Levin, P.; Galiana, D.; Volff, J.-N.
Abstract: Viruses and transposable elements, once considered as purely junk and selfish sequences, have repeatedly been used as a source of novel protein-coding genes during the evolution of most eukaryotic lineages, a phenomenon called 'molecular domestication'. This is exemplified perfectly in mammals and other vertebrates, where many genes derived from long terminal repeat (LTR) retroelements (retroviruses and LTR retrotransposons) have been identified through comparative genomics and functional analyses. In particular, genes derived from gag structural protein and envelope ( env ) genes, as well as from the integrase-coding and protease-coding sequences, have been identified in humans and other vertebrates. Retroelement-derived genes are involved in many important biological processes including placenta formation, cognitive functions in the brain and immunity against retroelements, as well as in cell proliferation, apoptosis and cancer. These observations support an important role of retroelement-derived genes in the evolution and diversification of the vertebrate lineage.